How did autistic children, and their parents, experience school transition during the Covid‐19 pandemic?. (28th April 2022) - Code, Aimee; Fox, Laura; Asbury, Kathryn; Toseeb, Umar
Abstract : Due to the Covid‐19 pandemic, the start of the academic year in September 2020 was a unique time for those transitioning to a new school. This study aimed to explore the experiences of parents who supported autistic children making a range of different school transitions in 2020. Semi‐structured interviews were carried out with 13 parents of autistic children in the UK, and data were analyzed with reflexive thematic analysis. For some parents, the Covid‐19 pandemic negatively impacted on aspects of school transitions. However, other parents expressed the view that these same circumstances created opportunities to approach the school transition in a unique, improved manner. This article sheds light on the heterogeneity of experiences and perceptions of parents of autistic children, and highlights the need to examine the impact of Covid‐19 on school transitions, including practices that it may be advantageous to retain.